The formation of Christendom - Allies, T. W. (Burns & Oates, 1887)
v. 1, The Christian faith and the individual.- v. 2, The Christian faith and society.- v. 3, The Christian faith and philosophy.- v. 4, As seen in church and state.- v. 5, The throne of the fisherman built by the Carpenter's son, the root, the bond and the crown of Christendom.- v. 6, The holy see and the wandering of the nations: Leo I to Gregory I.- v. 7, Peter's rock in Mohammed's flood: Gregory to Leo III.- v. 8, The monastic life, from the Fathers of the desert to Charlemagne.